Reading Tan Malaka's ideas in the context of Indonesian constitutional law - Yuwono, Ardi Tri; Bruijns, Peet (Priviet Social Sciences Journal, 2026)
The Indonesian Constitution faces various challenges, such as the potential for politicization, the court's dependence on state funding, and the public’s poor understanding of the constitutional judicial order. This study aims to provide a critical framework for studying Indonesian constitutionality from Tan Malaka's perspective. By using a philosophical-doctrinal approach combined with a critical textual analysis of Tan Malaka's key works, such as Madilog, Naar de Republiek Indonesia, and Gerpolek, as well as the Decision of the State Administrative Court Number 210/G/2021/PTUN.JKT, this study shows how its concepts of "100% independence" and "pseudo-independence" reveal the economic determinants of judicial and constitutional failures. The application of Madilog (Materialism, Dialectics, and Logic) of Tan Malaka as a methodological lens to deconstruct legal formalism and reveal the persistence of economic structures in state governance. True judicial independence requires institutional and budgetary autonomy for the Supreme and Constitutional Courts, which are protected from executive influence. Therefore, an interpretive canon based on Madilog is needed for Article 33 of the 1945 Constitution, prioritizing substantive social justice over formalism.